Influence of processing parameters on micro-perforated with ultrashort pulses (2011)
In this work ultra-short laser pulses (110 fs, 1 kHz; up to 1.1 mJ / pulse) were used for the micro-perforated steel. The processing with these pulses allowed to obtain circular holes, with precise measurements and without appreciable mechanical or chemical alteration of the adjacent areas. The holes were made using the optical treping system (Helical Drilling Optics, HDO) of the company TGSW-Stuttgart, which allowed to generate structures not only of great depth but also of variable diameter, thanks to the fact that up to three parameters of process simultaneously (speed of rotation of the beam, inclination and offset of the beam with respect to the optical axis) while the processing was executed. In the present work the influence of the wavelength of the laser was mainly studied, in the geometry of the micro-perforations. For this, the micro-perforation was performed with laser pulses with the fundamental wavelength (λ = 790nm) and that of the second harmonic (λ = 395nm), a specific set of optical elements for the HDO was used in each case and they were compared the results obtained which showed that there are no notable advantages when using the second harmonic. Deficiencies in the experimental device that prevented the influence of the wavelength with total precision are mentioned.